Ecologic and economic aspects of AAES creation - Mokin, B. I. (Visnyk of Vinnytsia Politechnical Institute, 2010)
Ecologic and economic prospects of addition to EES energy accumulators of AAES-class are investigated. Functional schemes of WES-AAES complexes, economic and mathematical models for their analysis are suggested.